Impact of Community Empowerment on Diarrhea Prevention Through Food Safety (A Case Study) - Nurita Lastri Tampubolon; Muhammad Hanri (Journal of Universal Community Empowerment Provision, 2026)
Community empowerment plays an important role in preventive public health interventions, particularly in reducing foodborne diseases such as diarrhea, which remains a major health burden in Indonesia. The Safe Food Village Program (Program Desa Pangan Aman), initiated by the Indonesian Food and Drug Authority (Badan Pengawas Obat dan Makanan), aims to improve food safety awareness and community capacity through empowerment-based interventions. This study examines the impact of the program on diarrhea incidence and evaluates its economic benefits. A quasi-experimental impact evaluation design using observational secondary data was employed, integrating administrative data from BPOM, Village Potential Statistics (Podes) 2018–2019, and the National Socioeconomic Survey (Susenas) 2019. To address non-random program participation, Mahalanobis Distance Matching (MDM) with Kernel weighting was used as the primary estimation model, complemented by regression adjustment and robustness testing using Propensity Score Matching (PSM) Kernel and Ordinary Least Squares (OLS). The findings indicate that participation in the Safe Food Village Program significantly reduced the diarrhea incidence ratio by 0.0085 percentage points (ATT = −0.000085) at the 1% significance level. Although modest in magnitude, the effect is epidemiologically meaningful at the national scale due to the large population coverage. The cost-benefit simulation further shows a positive net benefit of IDR 72.94 billion, with a Benefit-Cost Ratio of 7.63, indicating strong economic feasibility. These findings suggest that community-based food safety interventions can improve public health outcomes while generating substantial economic returns.